Evaluasi Undang-Undang No. 13 Tahun 2003 Terhadap Perlindugan Hak-Hak Tenaga Kerja Di Provinsi Banten - Dwi Noviati; Nurmalasari; Mariyah Ulfah; Annaelmyra Hawa; Enjum Jumhana (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2025)
This study uses a descriptive qualitative method, with a systematic literature review approach. Data collection techniques are based on literature studies. With this, the collection of research data using literature studies through literature studies from various appropriate reference sources from journals, books, and internet sources to conduct analysis and classification of the issues or topics being studied. This study uses evaluation theory, because it focuses on the extent to which the policy of Law No. 13 of 2003 has been achieved regarding the protection of labor rights in Banten Province. The results of the study related to the Evaluation of Law No. 13 of 2003 Regarding the Protection of Labor Rights in Banten Province show that it has not been running well and is also not optimal. Where there are still many obstacles that occur in implementing the Law as a legal basis for meeting the needs of the workforce as the purpose of the implementation of Law No. 13 of 2003.